2009
DOI: 10.1002/med.20163
|View full text |Cite
|
Sign up to set email alerts
|

Falcipain‐2 inhibitors

Abstract: Malaria, particularly that one caused by Plasmodium falciparum, remains a serious health problem in Africa, South America, and many parts of Asia where it afflicts about 500 million people and is responsible for the death of more than one million children each year. The main reasons for the persistence of malaria are the emergence of resistance to common antimalarial drugs, inadequate control of mosquito vectors, and the lack of effective vaccines. Therefore, the identification and characterization of new targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
108
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 139 publications
1
108
0
Order By: Relevance
“…This, in turn, guided the identification of the potential mode of action for these compounds to be through the inhibition of falcipain 2 in the food vacuole. Interestingly, the structure of the series does not contain the typical pharmacophore of cysteine protease inhibitors, and the apparent disconnect between falcipain 2 inhibition and whole-cell activity may be explained by the presence of two basic amines that would allow the compounds to be concentrated in the acidic food vacuole by a pH gradient (51). Further studies might investigate the morphological changes to the parasite induced by compounds of the 1,2,4-oxadiazole series, as falcipain inhibitors have previously been associated with impaired hemoglobin digestion, which was visible by light microscopy (52).…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, guided the identification of the potential mode of action for these compounds to be through the inhibition of falcipain 2 in the food vacuole. Interestingly, the structure of the series does not contain the typical pharmacophore of cysteine protease inhibitors, and the apparent disconnect between falcipain 2 inhibition and whole-cell activity may be explained by the presence of two basic amines that would allow the compounds to be concentrated in the acidic food vacuole by a pH gradient (51). Further studies might investigate the morphological changes to the parasite induced by compounds of the 1,2,4-oxadiazole series, as falcipain inhibitors have previously been associated with impaired hemoglobin digestion, which was visible by light microscopy (52).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most studies in this area have shown that falcipain inhibitors prevent hemoglobin hydrolysis, block parasite development and cure murine malaria [11][12][13]. Moreover, the combination of high-throughput screening, molecular modeling methods and the availability of X-ray structures of falcipains has contributed to the discovery of potent inhibitors able to inactivate these Pf enzymes in a reversible or irreversible manner [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…To increase both bioavailability and aqueous solubility, several structural replacements on K11017 were tested [15]. Although some compounds demonstrated better activities than the parent molecule, they also revealed limited utility as therapeutic agents due to their susceptibility to protease degradation and their poor absorption through cell membrane [14]. In an effort to well define the structure-activity relationships of this class of compounds, Shenai et al recently disclosed a new series of 39 new vinyl sulfone, vinyl sulfonate ester, and vinyl sulfonamide cysteine protease inhibitors and determined their FP2 inhibitory activity [16].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the disruption of FP2 gene revealed that the loss of this enzyme alone is not sufficient to cause parasite lethality, thus suggesting the participation of additional cysteine proteases for parasite invasion and growth in human erythrocytes [86]. In contrast, the FP3 gene could not be disrupted, revealing that FP3 is essential to erythrocytic parasites and therefore indicating that efforts to develop cysteine protease inhibitors as antimalarial drugs should probably be focused on FP2 and FP3 [86]. The structural similarities of FP2 and FP3 can be a reason for these proteases performing similar functions in the FV.…”
Section: Cysteine Proteases (Falcipains)mentioning
confidence: 99%
“…Although both FP2 and FP3 contribute almost equally to the digestion of hemoglobin, FP3 is usually less amenable to inhibition by peptidyl-based small molecules [83]; consequently, there is a variety of FP2 inhibitors in the literature [86]. In general, FP inhibitors can be classified in peptidylbased inhibitors (covalent irreversible and reversible inhibitors) [83,90,91], including peptidomimetic compounds [92,93], and nonpeptidic small inhibitors [94][95][96].…”
Section: Cysteine Proteases (Falcipains)mentioning
confidence: 99%